Growth performance, hemato-biochemical indices, thyroid activity, antioxidant status, and immune response of growing Japanese quail fed diet with full-fat canola seeds - Abdel-Moneim, Abdel-Moneim E.; Sabic, E. M.; Abu-Taleb, A. M.; Ibrahim, N. S. (Tropical animal health and production, 2020)
Dietary supplementation of full-fat canola seeds (FFCS) can be part of the global solution to the problem of incessant raise in feed cost. Genetic improvement via plant breeding constantly introduces varieties of canola with higher content of unsaturated fatty acids and lower content of anti-nutritional factors. This experiment was conducted to evaluate the dietary inclusion effect of new mutant of FFCS on growth performance, carcass traits, blood metabolites, thyroid activity, antioxidant status, and immune response of growing Japanese quails. A total of 640 21-day-old quails were used in a completely randomize design with and equally allotted to four experimental groups and eight replicates each. The experimental groups fed diets supplemented with 0, 50, 100, and 150 g FFCS/kg diet from 21 to 49 days of age. All experimental diets were isocaloric and isonitrogenous. The inclusion level of FFCS did not affect body weight and body weight gain at all studied periods, while feed intake was reduced and feed conversion ratio was enhanced linearly under all experimental periods except the duration from 28 to 35 days of age. All carcass traits were not statistically affected with graded levels of FFCS. Hemoglobin, leucocytes, mean corpuscular hemoglobin (MCH), and MCH concentration values were linearly increased. Serum protein fractions, liver enzymes activities, renal function biomarkers, and triiodothyronine concentration were not affected. However, serum lipid profile was significantly altered, where high-density lipoprotein was linearly increased while triglycerides and low-density lipoprotein (LDL) were linearly (and quadratically for LDL) decreased. Antioxidant and immune statuses were improved; significant increment in glutathione and glutathione peroxidase values and antibody titer against Newcastle disease virus were elevated in groups treated with 10% and 15% FFCS. In conclusion, studied levels of FFCS, however, were not able to promote the growth rate of growing Japanese quails; they were more effective in boosting their antioxidant status and humoral immune response.